2004
DOI: 10.1002/jssc.200301625
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of proteinaceous binders in artistic paintings by chromatographic techniques

Abstract: This review discusses the application of chromatographic techniques (GC, HPLC and Py-GC) for the characterisation of proteinaceous materials in artistic paintings. The focus is on the various analytical steps that are needed to determine these natural materials in paint samples, from sampling and sample pre-treatment, including various methods of hydrolysis and derivatisation for GC and HPLC, to approaches for data evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
75
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 82 publications
(124 reference statements)
5
75
0
Order By: Relevance
“…The methods have been evaluated statistically, by means of the principal component analysis (PCA), which is a multivariate method preferred in comparing samples of known composition with unknown samples [3,5,9,11,15,50]. By PCA it is often possible to represent objects and categories of objects in terms of a few dimensions, without great loss in the information content provided by the original experimental variables [29].…”
Section: Pcamentioning
confidence: 99%
“…The methods have been evaluated statistically, by means of the principal component analysis (PCA), which is a multivariate method preferred in comparing samples of known composition with unknown samples [3,5,9,11,15,50]. By PCA it is often possible to represent objects and categories of objects in terms of a few dimensions, without great loss in the information content provided by the original experimental variables [29].…”
Section: Pcamentioning
confidence: 99%
“…29 Analyses of oxygenated triglycerides and phosphatidylcholines in solid egg films have indicated that with exposure to light oxygen is introduced without addition or abstraction of hydrogen, with the formation of structures such as hydroxides, epoxides, hydroperoxides and epidioxides. 16 In proteins, on the other hand, lysine and tyrosine are the amino acids most susceptible to photodegradation.…”
Section: Introductionmentioning
confidence: 99%
“…The range of chromatographic techniques applied to the characterisation of the proteinaceous constituents in paint includes paper chromatography [32,33], thin-layer chromatography (TLC) [34][35][36], ionic exchange chromatography [37,38], reversed phase high-performance liquid chromatography with pre-column derivatisation [14,[39][40][41][42][43][44][45], gas chromatography [7,15,16,30,[46][47][48][49][50][51][52][53][54][55][56][57], and pyrolysis combined with gas chromatography-mass spectrometry (Py-GC/MS) [58][59][60][61][62][63][64][65][66]. Gas chromatography (GC) and gas chromatography-mass spectrometry (GC/MS) are among the most commonly used techniques for the identification of proteinaceous paint media, and they generally give more accurate and reliable results than other methods due to their high specificity and sensitivity [5,11,67].…”
Section: Action Induced By Environmental Conditionsmentioning
confidence: 99%
“…Another advantage of using mass spectrometric detection is that it can distinguish analytes tagged with stable isotopes, offering the possibility to use them as internal standards for quantification. Using MS can have a great effect on the specificity and sensitivity of detection [5,11,68], and can be further enhanced whenever a derivatisation reaction is applied in the chromatographic protocol. This unique aspect of the detection specificity and sensitivity, together with the increased availability of low cost affordable systems, makes it clear why these techniques are so frequently used.…”
Section: Action Induced By Environmental Conditionsmentioning
confidence: 99%
See 1 more Smart Citation